The Impact of Knowledge Management Processes on Organizational Creativity: A Field Study on a Municipal Agency Governorates in Jeddah Municipality - Al-Salami, Hamdan Sweiher Hamid; Shuaibi, Faisal Ahmed (The Arab Journal of Administration, 2025)
This study aimed to identify the reality of knowledge management in the Governorate Municipalities Agency in the Municipality of Jeddah, and to determine the impact of knowledge management on organizational creativity from the employees’ point of view, and to identify the impact of knowledge management on organizational creativity due to the variables of gender, age, academic qualification and job experience. Relying on the descriptive approach, the questionnaire was used as a tool for collecting data from the 190 directors of the Governorate Municipalities Agency in Jeddah Municipality. This issue was obtained from the Human Resources Department at the Provincial Municipalities Agency in the Municipality of Jeddah on 5/11/1443 AH, where the researcher applied the comprehensive inventory to the entire study population. Impact on organizational creativity in its dimensions (fluency, originality, flexibility The results of the study showed that the employee can deal with technological means in disseminating knowledge by using databases to save information. To perform the work entrusted to him in multiple and distinct ways, and he can impose his opinion with evidence and arguments, and that he can adapt to various new ways of working, and works to develop work. Among the recommendations, the employee should choose the required sources of knowledge and the need to find dealings with different sources of knowledge to acquire them. As well as for the employee to work on documenting the knowledge that he possesses.